CO2 ablative fractional laser - mechanism of action and assessment of safety, effectiveness in the treatment and possible side effects based on a review of scientific literature - Kołodziejczyk, Kacper; Hop, Izabela; Branewska, Justyna; Ostrowska, Barbara; Matysek, Mikołaj; Olszanicka, Anna; Imioło, Jan; Maciąg, Anna; Niemiec, Rafał; Galas, Adam (Journal of Education, Health and Sport, 2023)
Introduction: Laser therapy has been used in medicine for many years. One of the most willingly used is the fractional ablative CO2 laser. As a result of its use, the improvement of pigmentation, skin texture and signs of aging are achieved. Laser therapy owes its popularity to its low invasiveness and good, long-lasting effects of the procedure. Despite its important role in aesthetic medicine, we should not forget about its participation in the treatment of scars, often extensive, causing troublesome symptoms to patients, the source of which is not only a defect of a cosmetic nature. Purpose of the work: The purpose of the study is to present mechanism of action, assessment of safety, effectiveness in the treatment and possible side effects based on a review of scientific literature. Material and methods: The work was based on a review of available medical publications on the use of the fractional ablative CO2 laser. The literature in the PubMed and Google Scholar databases was searched based on the following keywords: fractional ablative CO2 laser, mechanism of action, safety of use, side effects. Conclusion: The use of a fractional ablative CO2 laser causes the increased collagen production in the dermis. This effect contributes to the elevation of the quantity and level of collagen arrangement, and also to the reduction of the visibility of the effects of photoaging. As a result, the skin in the treated area becomes thicker, and thus firmer. The pigmentation and texture are also being improved. The procedure is relatively slightly invasive, and the side effects are self-limiting in the most cases.